Expectancy-value theories applied in Korean physical activity contexts: a meta-analysis - Song, Jihyun; Choi, Wonseok (Frontiers in Psychology, 2025)
IntroductionRecognizing expectancy-value theory as an influential framework for explaining the mechanism of motivation, relevant research has increased in physical activity contexts. This theory assumes that individuals’ motivation is situated and context-specific, shaped by the culture in which they live. Guided by expectancy-value theory, the purpose of this study was to synthesize the determinants and outcomes of motivation in Korean physical activity contexts through a meta-analytic approach.MethodsFollowing the PRISMA statement, this study performed a comprehensive literature search in five electronic databases by May 21, 2025. After extracting and collecting data from the included studies, a meta-analysis was carried out in the R software with the heterogeneity test, publication bias assessment, and subgroup analysis.ResultsThe findings demonstrated moderate-to-strong effects of the relationships between expectancy-value theory-based motivation and its determinants and outcomes, suggesting that individuals’ motivation was shaped by different internal and external factors, such as motivational constructs, social-contextual influences, and task difficulty, and contributed to affective experiences and behavioral engagement. Self-perceptions were likely to serve as a determinant of expectancy beliefs and an outcome of task values.ConclusionThese findings suggest both cross-cultural patterns and distinct mechanisms of expectancy-value theory-based motivation in physical activity contexts.